Evaluation of the gliding capacity of a swimmer - Roig, A. (Biomechanics and Medicine in Swimming XI, 2010)
Reducing resistance is probably the fastest way to improve performance and the most efficient to reduce energetic cost. Therefore, the aim of this study was twofold: (i) to give advice to coaches to re-orient their training sessions towards reduction of resistance forces and suggest exercises for its improvement and, (ii) to develop and apply a new test for the evaluation of gliding. The proposed gliding test evaluated the maximum speed reached by the swimmer after push-off and the passive hydrodynamic resistance when gliding through the water. A well-balanced solution between accuracy, validity and applicability for the evaluation of underwater glide was found.